A COMPREHENSIVE REVIEW OF INTERACTIVE DIGITAL EXHIBITION DESIGN BASED ON VISITOR EXPERIENCE - He, Qiying; Kosenko, Danylo Yuriiovych (Theory and practice of design, 2024)
Purpose. This paper provides a comprehensive review of interactive digital exhibition design, focusing on audience experience. It aims to map the evolution of these exhibitions, assess the impact of design elements, and explore future implications. Methodology. The review employs a chronological approach, analyzing academic articles and conference proceedings. It integrates interdisciplinary aspects like design, technology, and psychology, identifying research gaps and future directions. Results. Key observations include the evolution from technology-centric to user-centric design, and the growing integration of psychology into design. It underscores the importance of a unified theoretical framework and diverse visitor needs in future research. Scientific novelty lies in its comprehensive, chronological approach and the integration of various disciplines, providing a new perspective on the evolution and future of interactive digital exhibition design. Practical significance. This review serves as a resource for researchers, designers, and museum professionals, guiding the design of interactive digital exhibitions to enhance audience engagement and experience.